Doses crescentes de calcário e gesso agrícola num latossolo vermelho eutroférrico e alterações químicas do solo, planta e de caracteres agronômicos da canola - Mascarello, Guilherme (2019)
Tropical soils are characterized by low natural fertility and high levels of Al and Fe. Under these conditions, the use of correctives and soil conditioners are fundamental to correct the acidity and to provide nutrients. The objective of this work was to evaluate the effects of the application of lime and gypsum on the soil pH, foliar content of nutrients and the agronomic characteristics of Hyola 433 hybrid. The experiment was carried out in polyethylene pots of 5 dm3, in protected cultivation in the municipality of Marechal Cândido Rondon during the years 2017 and 2018, where a RED LATOSOL was used as substrate. The experimental design was a randomized complete block design with four replicates, in a 4 x 4 factorial scheme, with four doses of lime (0, 325, 650 and 1300 mg dm-3) and four doses of gypsum (0, 125, 250 and 500 mg dm-3). The application of gypsum did not significantly influence the variables analyzed during the two years of experimentation. The application of lime in the canola crop implied a linear increase in soil pH, and for each 100 mg dm-3 of limestone applied, it is estimated an increase of 0,08 and 0,03 in soil pH in the years 2017 and 2018, respectively. Likewise, the application of lime resulted in increased leaf contents of K, Ca and Mg, with a linear increase, where the highest dose applied (1300 mg dm-3) resulted in the highest levels of these nutrients. Linear increases were also verified for biometric and agronomic characteristics of the canola crop, and for the AP applying the highest dose (1300 mg dm-3) a AP of 27 cm was obtained, being approximately 8% higher than the control (without application of lime). The increase also occurred in a linear way for the NGS and MMG when increasing doses of lime were applied, and a dose of 1300 mg dm-3 of limestone was obtained with 16 grains per siliqua (NGS) and an MMG of approximately 3,57 g, those values being 23 and 17% higher than the control. There was no significant increase in productivity with regard to the application of lime and gypsum, and the average productivity of the years 2017 and 2018 was 6.57 g plant-1.